John Rawls’ Theory of Justice: Relevance to Nigeria Ethno-Religious Challenges (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2025)
Since gaining independence in 1960, Nigeria has struggled with ethnic and religious tensions that hinder national development. With over 250 ethnic groups and a nearly equal Muslim-Christian population, historical grievances, economic disparities, and political exploitation fuel conflicts that threaten stability. Ethnic rivalries, particularly among the Hausa-Fulani, Yoruba, and Igbo, intersect with religious divisions, often leading to violence. Politicians frequently manipulate these divisions to gain power, exacerbating instability. This study applies John Rawls’ principles of justice—equal basic liberties and the difference principle—to assess how ethnicity and religion create “unjust inequalities” in Nigeria’s governance. It explores key questions: How do ethnic and religious affiliations shape political and economic inequalities? Why do politicians exploit these divisions? What constitutes secularity in a multi-religious society? Using an analytical approach, the research argues that a secular framework, which separates religion from politics, is essential for ensuring justice and equal rights for all citizens. Drawing insights from Rwanda’s post-genocide reconciliation and other global cases, the study proposes strategies for fostering unity and reducing conflict. While advocating for inclusive governance, it also considers separation as a last resort, referencing historical examples such as India-Pakistan, Yugoslavia, Sudan, and Cyprus. Ultimately, the research highlights the urgent need for policies that transcend ethnic and religious affiliations to promote stability, economic growth, and national cohesion.